2015
DOI: 10.1371/journal.pone.0115290
|View full text |Cite
|
Sign up to set email alerts
|

Poverty, Food Insufficiency and HIV Infection and Sexual Behaviour among Young Rural Zimbabwean Women

Abstract: BackgroundDespite a recent decline, Zimbabwe still has the fifth highest adult HIV prevalence in the world at 14.7%; 56% of the population are currently living in extreme poverty.DesignCross-sectional population-based survey of 18–22 year olds, conducted in 30 communities in south-eastern Zimbabwe in 2007.ObjectiveTo examine whether the risk of HIV infection among young rural Zimbabwean women is associated with socio-economic position and whether different socio-economic domains, including food sufficiency, mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
77
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(87 citation statements)
references
References 65 publications
(82 reference statements)
8
77
0
2
Order By: Relevance
“…Third, between half and two-thirds of adolescents reported having an older sexual partner during first sex, which is linked to reduced condom use in the general adolescent population [68]. Fourth, one in five participants reported engaging in transactional sex or having sex for money or goods–a sexual practice associated with unprotected sex [82], a result that was consistent across multiple studies [63,73,75]. HIV-positive adolescent girls reported a higher prevalence of transactional sex, having older sexual partners, and unprotected sex, though adolescent boys were more likely to report early sexual activity and multiple sexual partners.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Third, between half and two-thirds of adolescents reported having an older sexual partner during first sex, which is linked to reduced condom use in the general adolescent population [68]. Fourth, one in five participants reported engaging in transactional sex or having sex for money or goods–a sexual practice associated with unprotected sex [82], a result that was consistent across multiple studies [63,73,75]. HIV-positive adolescent girls reported a higher prevalence of transactional sex, having older sexual partners, and unprotected sex, though adolescent boys were more likely to report early sexual activity and multiple sexual partners.…”
Section: Resultsmentioning
confidence: 91%
“…Sixth, studies testing for biomarkers of HSV-2 and HPV found 50% and 88% infection rates in HIV-positive adolescents, respectively [57,73]. This suggests high levels of unprotected sex and higher risk for co-infection with other sexually transmitted infections.…”
Section: Resultsmentioning
confidence: 99%
“…Probiotic microorganisms have been shown to have prophylactic and therapeutic effects against gastrointestinal diseases, particularly diarrhoea. With a high HIV prevalence rate (15.2% in the 15-49 years age group; 2015 data) [3], erratic outbreaks of diarrhoeal diseases [4,5] and high prevalence of sexually transmitted infections [6] that collectively co-occur with poverty [7], the use of complementary diets and medicines has remained central to maintaining wellness and treatment of diarrhoea among many residents of Zimbabwe.…”
Section: A Rt I C L E I N F O Abstractmentioning
confidence: 99%
“…Evidence examining exposure to sexual risk has largely focused on 15-to 24-year-old adolescent girls and young women, particularly given the strong association between sexual risk exposure and heterosexual HIV infection in this population in sub-Saharan Africa [7][8][9]. Early sexual debut, sex in exchange for goods or money, and age-disparate relationships among young women and older sexual partners also contribute to high HIV infection risk [10][11][12][13][14][15][16], including unintended pregnancies [17].…”
Section: Introductionmentioning
confidence: 99%